Thabit Ibn Qurra : History and The Influence to Detemine The Time of Praying Fardhu - Febriawan, Muhamad Rizky; Pangestu, Saka Aji (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The application of mathematical history for overcoming with life’s problems are reflection to build more advanced civilizations than previous civilizations, because by studying history a nation can do an evaluation of the past mistakes. In addition, mathematical history gives wide basic understanding against the mathematical consepts for giving a solution against the problems. Not only about the ideal world held by the Platonist. As example, in the golden age of islam, the scientist at that moment developed knowledge especially mathematics with the principal to solve the problems with in daily life. The one of them is Thabit ibn qurra. Thabit ibn qurra used the principal of geometry to decide motion of the sun. The method used was by means of a shadow that produced by sunlight. So, the muslim can pray fardhu on time. This research is meant to reconstruct the method was used by Thabit ibn qurrah, so that the mathematics especially, the topic of geometry is no longer a matter that cannot be expressed in real or real terms. So that, the young generations, especially muslim will realize that learn the mathematics is invaluable in this life. Not only for them self but also to give benefits for a lot of people. The result is the young generations will have the spirit to learn it. The method was used in this research is the study of literature, which mean to study the relevant previous researches and conclude based on the data obtained. The result of this research Thabit’s discovery of influences on prayer time determination.